2022
DOI: 10.1126/sciadv.abm7375
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and specificity of inhibitors of BCL-2 family protein interactions assessed by affinity measurements in live cells

Abstract: Cytoplasmic and membrane-bound BCL-2 family proteins regulate apoptosis, a form of programmed cell death, via dozens of binary protein interactions confounding measurement of the effects of inhibitors in live cells. In cancer, apoptosis is frequently dysregulated, and cell survival depends on antiapoptotic proteins binding to and inhibiting proapoptotic BH3 proteins. The clinical success of BH3 mimetic inhibitors of antiapoptotic proteins has spawned major efforts by the pharmaceutical industry to develop mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 88 publications
3
29
2
Order By: Relevance
“…1 D ). As expected, binding to the wildtype V BCL-XL and V BCL-2, known to bind BIK in live cells ( 52 ), resulted in binding curves with higher FRET efficiency that also saturate when the acceptor:donor ratio is greater than 1. In contrast, primarily collisions were detected for the negative binding control, C BIK-L61G.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…1 D ). As expected, binding to the wildtype V BCL-XL and V BCL-2, known to bind BIK in live cells ( 52 ), resulted in binding curves with higher FRET efficiency that also saturate when the acceptor:donor ratio is greater than 1. In contrast, primarily collisions were detected for the negative binding control, C BIK-L61G.…”
Section: Resultssupporting
confidence: 73%
“…Further delineation of how and where these interactions occur is an important step for understanding BCL-2 family protein function. When expressed in live cells, BIK with an N-terminally fused fluorescent protein remains functional ( 52 ). We recently demonstrated that in live cells a fluorescent protein fusion of BIK binds to BCL-2, BCL-XL, and BCL-W with high affinity and MCL-1 with lower affinity ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations